Teaching information security management: reflections and experiences. Issue 5 (10th November 2014) - Ahmad, Atif; Maynard, Sean
Abstract : Purpose: – The purpose of this paper is to describe the development, design, delivery and evaluation of a postgraduate information security subject that focuses on a managerial, rather than the more frequently reported technical perspective. The authors aimed to create an atmosphere of intellectual excitement and discovery so that students felt empowered by new ideas, tools and techniques and realized the potential value of what they were learning in the industry. Design/methodology/approach: – The paper develops fundamental principles and arguments that inform the design and development of the teaching curriculum. The curriculum is aimed at security management professionals in general and consultants in particular. The paper explains the teaching method in detail including the specific topics of lectures, representative reading material, assessment tasks and feedback mechanisms. Finally, lessons learned by the authors and their conclusions are presented as a form of reflection. Findings: – The instructors recognized four key factors that played a role in the atmosphere of intellectual excitement and motivation. These were new concepts and ideas, an increased level of engagement, opportunities for students to make their own discoveries and knowledge presented in a practical context. Maintaining a high quality of teaching resources, catering for diverse student needs and incorporating learning cycles of assessment in a short period of time were additional challenges. Originality/value: – Most "information security" curricula described in research literature take a technology-oriented perspective. This paper presents a much-needed management point of view. The teaching curriculum (including assessment tasks) and experiences will be useful to existing and future teaching and research academics in "information security management". Those interested in developing their own teaching material will benefit from the discussion on potential topic areas, choice of assessment tasks and selection of recommended reading material.